2014
DOI: 10.1097/sle.0b013e31828f6bc0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Conversion in Laparoscopic-assisted Colectomy for Colorectal Cancer and Clinical Outcomes

Abstract: This study investigated risk factors and impact of open conversion on outcomes of 207 consecutive patients who had laparoscopic resection of colorectal cancer at our institution. Conversion occurred in 15.9% of patients, mostly because of invasion to adjacent structures (30.3%), bulky tumor (21.2%), and adhesions (18.2%). Converted patients had significant larger tumor size, advanced stage, increased operative blood loss, time to walk independently, prolonged hospital stay, number of massive hemorrhage, ileus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 2 publications
2
35
0
7
Order By: Relevance
“…Previous studies have demonstrated better clinical short-term outcomes with the laparoscopic approach [11][12][13], while other studies have shown marginal or no short-term clinical benefits [14][15][16]. Bearing in mind that laparoscopic appendectomy, unlike other laparoscopic procedures, has not been found superior to open surgery for acute appendicitis [17]. Therefore, we conducted the present meta-analysis to compare the short-term outcomes (wound infection, intra-abdominal abscess, postoperative complications, peritonitis, postoperative ileus, urinary tract infection, and reoperation) between open appendectomy and laparoscopic appendectomy (LA) in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated better clinical short-term outcomes with the laparoscopic approach [11][12][13], while other studies have shown marginal or no short-term clinical benefits [14][15][16]. Bearing in mind that laparoscopic appendectomy, unlike other laparoscopic procedures, has not been found superior to open surgery for acute appendicitis [17]. Therefore, we conducted the present meta-analysis to compare the short-term outcomes (wound infection, intra-abdominal abscess, postoperative complications, peritonitis, postoperative ileus, urinary tract infection, and reoperation) between open appendectomy and laparoscopic appendectomy (LA) in adults.…”
Section: Introductionmentioning
confidence: 99%
“…LAS is rapidly becoming the standard of care for colorectal malignancies. Previous reports demonstrated that one of the major reasons for conversion to laparotomy was adhesions (6). However, the guideline from the European Association of Endoscopic Surgery mentioned that a history of prior abdominal surgery did not influence the conversion rate or the complication rate (7).…”
Section: Discussionmentioning
confidence: 99%
“…По мнению ряда авторов, лапароскопическая резекция кишки может быть неэффективной при выраженном спаечном процессе после ранее выполненных вмешательств [11,15,16]. Однако не все авторы придерживаются такого мнения [17], кроме того, изучается зависимость частоты конверсий доступа от объема и тяжести ранее выполненной операции.…”
Section: Discussionunclassified